Finding our true north: On languages, understanding and curriculum in Northern Ireland. Issue 3 (28th December 2020) - Jones, Sharon
Abstract: Language learning can open up new worlds and deepen understanding of our own. It can foster awareness of other people, other places and cultures, and bring social and educational benefits. Northern Ireland (NI) is an increasingly multilingual region that is emerging from conflict into a welcome, but fragile, peace. It faces unique uncertainties caused by Brexit, as well as the need to develop empathy in face of the COVID‐19 pandemic. Concerns have been expressed also about academic underachievement and mental health amongst its young people. Against such a background, this paper explores the current context in NI relating to languages, and curriculum policy and practice in language education. It argues that young people in NI are poorly served, and that curriculum reform with respect to languages is timely. The paper makes five key recommendations: (1) Reform of curriculum, policy and practice relating to language education in NI; (2) Introduction of statutory language learning in primary schools; (3) Investment in teacher development; (4) Valuing of linguistic diversity and plurality in curriculum policy and practice; and (5) Further practice‐based research to explore pedagogy and outcomes in language education in NI.